Analisis Pemenuhan Standar Sarana dan Prasarana Sekolah - Nina Lamatenggo; Irun Abubakar; Intan Abdul Razak (PEDAGOGIKA, 2020)
The purpose of this study was to determine the fulfillment of facilities and infrastructure of general learning spaces, supporting spaces and special learning spaces at SMK Almamater Telaga. This type of research is quantitative with the type of descriptive research. Data collection techniques using interviews, observation, data collection instruments and documentation. The results of the study are 1) the facilities and infrastructure of the general learning space are met according to the standards, and not according to the standards namely Biology Lab, Physics Lab, Chemistry Lab, Natural Sciences, Language Lab and technical drawing practice room. Whereas the facilities for 2 classrooms are in accordance with the standard and 13 classrooms, the library, and the computer lab are not yet in accordance with the standard, 2) the supporting facilities and infrastructure are met according to the standard, toilets, counseling rooms, UKS, and circulation rooms not according to standards, 3) facilities and special learning space infrastructure are not yet up to standard. Suggestions in this research are to pay more attention to the development of LAB infrastructure in Chemistry, Biology, Physics, Science, Technical Drawing Practice Room, Counseling Room, UKS Room and circulation room. In addition, the area of special learning space for all majors is adjusted according to the work area of each department.